2020
DOI: 10.1021/acsami.9b17168
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Silver Nanowire Transparent Conducting Electrodes for Thin-Film Solar Cells

Abstract: Silver nanowire (AgNW) networks have demonstrated high optical and electrical properties, even better than those of indium tin oxide thin films, and are expected to be a next-generation transparent conducting electrode (TCE). Enhanced electrical and optical properties are achieved when the diameter of the AgNWs in the network is fairly small, that is, typically less than 30 nm. However, when AgNWs with such small diameters are used in the network, stability issues arise. One method to resolve the stability iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 44 publications
(55 reference statements)
0
43
0
Order By: Relevance
“…In 2019, Lee et.al. used electrodeposition of silver ions on spin coated AgNW TCE and demonstrated that this technique can enhance various optoelectronic properties such as electrical conductivity, optical transmittance, high temperature stability along with low junction height and sheet resistance [240]. Consequently, the obtained a TCE with a transmittance more than 93% and sheet resistance of 14 Ω/sq as shown in Figure 21f,g.…”
Section: Joule Heating and Electro-deposition Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…In 2019, Lee et.al. used electrodeposition of silver ions on spin coated AgNW TCE and demonstrated that this technique can enhance various optoelectronic properties such as electrical conductivity, optical transmittance, high temperature stability along with low junction height and sheet resistance [240]. Consequently, the obtained a TCE with a transmittance more than 93% and sheet resistance of 14 Ω/sq as shown in Figure 21f,g.…”
Section: Joule Heating and Electro-deposition Methodsmentioning
confidence: 94%
“…In 2019, Lee et.al. used electrodeposition of silver ions on spin coated AgNW TCE and demonstrated that this technique can enhance various optoelectronic properties such as electrical conductivity, optical transmittance, high temperature stability along with low junction height and sheet resistance [240]. Consequently, the obtained a TCE with a transmittance more than 93% and sheet resistance of 14 Ω/sq as shown in Figure 21f Recently, a highly flexible, transparent and conductive electrode with a negligible junction height was fabricated using spray coating under the application of low DC voltage (3.6-6.0 V) as shown in Figure 21b [238].…”
Section: Joule Heating and Electro-deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transparent conducting electrode (TCE) is an essential part of various optoelectronic devices such as lightemitting diodes, photovoltaic cells, touch screens, solar cells, and flat-panel displays [1][2][3]. Among various TCEs, Indium tin oxide (ITO) is most preferred as it wealth with attracting characteristics like high transmittance (~ 90%) and low sheet resistance (~ 10 Ω/sq.)…”
Section: Introductionmentioning
confidence: 99%
“…However, ITO application is limited by the high fabrication cost, while its brittleness makes it unsuitable for flexible electronics. Various alternative materials, such as carbon nanotubes [4,5], graphene [6,7], conductive polymers [8,9], and metallic nanowires [10,11] are being explored, among which silver nanowires (AgNWs) have attracted special attention because of their high electrical conductivity, high transparency, and excellent mechanical properties [1][2][3][12][13][14]. The most commonly used method of AgNWs synthesis is the polyol method, which is a simple, yet highly controllable liquid-phase process that does not require expensive equipment [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%